Co-occurrence of ectoparasites on rodent hosts: Null model analyses of data from three continents - Krasnov, Boris R. (2010)
We studied patterns of species co-occurrence in communities of ectoparasitic arthropods (ixodid ticks, mesostigmate mites and fleas) harboured by rodent hosts from South Africa (Rhabdomys pumilio), South America (Scapteromys aquaticus and Oxymycterus rufus) and west Siberia (Apodemus agrarius, Microtus gregalis, Microtus oeconomus and Myodes rutilus) using null models. We compared frequencies of co-occurrences of parasite species or higher taxa across host individuals with those expected by chance. When non-randomness of parasite co-occurrences was detected, positive but not negative co-occurrences of parasite species or higher taxa prevailed (except for a single sample of mesostigmate mites from O. rufus). Frequency of detection of non-randomness of parasite co-occurrences differed among parasite taxa, being higher in fleas and lower in mites and ticks. This frequency differed also among host species independent of parasite taxon, being highest in Microtus species and lowest in O. rufus and S. aquaticus. We concluded that the pattern of species co-occurrence in ectoparasite communities on rodent hosts is predominantly positive, depends on life history of parasites and may be affected to a great extent by life history of a host.